A Kanban Framework as a Systematic Approach for Reducing the Human Tendency to Resist Change - Fatma H. Fazzani; Khamisa A.Yousef (Wadi Alshatti University Journal of Pure and Applied Sciences, 2025)
The real success of developing any system is that the customer is satisfied and agrees with the system requirements specifications that were extracted from the requirements engineering stage. Requirements Engineering (RE)-related activities require high collaboration between various roles in software engineering (SE), such as requirements engineers, stakeholders, developers, etc. The development of requirements engineering methodologies has been of great importance in overcoming the problem of not accepting change for a customer when developing the system. Among these advanced methodologies the agile methodology that involves constant collaboration with stakeholders and continuous improvement at every stage the kanban process is one of agile methodologies that structured to address the human tendency to resist change. The main objective of this paper is to provide a kanban framework as a systematic approach that helps to reduce the human tendency to resist change.